Career Motivation in the Process of State Regulation of Youth Employment - Natalya Stativka; Anna Batiuk (Central European Public Administration Review)
Purpose: The main objective of the study is to find new methods for the state promotion of career motivation in the process of providing youth employment. Design/Methodology/Approach: To accomplish the research objectives, a set of mutually reinforcing general scientific and special research methods was used. The basic statistical analyses of unemployment rate data according to the methodology of the International Labour Organization, while the level of registered unemployment (the national indicator of the unemployment rate in Ukraine) serves as an indicator of the State Employment Service performance. Findings: A detailed analysis of career motivation theories and the technology of servicing potentially unemployed people helped justify the feasibility of applying a communicative and psychological method in employment center specialists’ work with their clients, in particular the youth. Thus, a number of measures were identified and proposed in order to better encourage employment and increase the effectiveness of career motivation. Practical Implications: In the course of the research, the development trends in the youth labour market of Ukraine were estimated, the main causes for youth unemployment were determined, and the value orientations and characteristics of modern youth were analysed. The importance of employment services focusing on effective communication with their clients to motivate them for successful employment and self-development is substantiated. The issues of young people’s migration activity, which can have a negative effect on the economic development of the country and increase the socio-demographic risks to national security, need a detailed scientific study. Originality/Value: Currently, the science of public administration does not pay due attention to the role of public institutions in providing career motivation or to the legal consolidation of the measures that motivate productive work. A vast majority of research works on professional motivation and career development were conducted by scientists from the fields of pedagogy, psychology and social economy. These works reveal the essence of pedagogical education and the peculiarities of human psychological influence, yet fail to define the role of the state as the main social institution which should lay the basis for youth development and encouragement to employment. This renders the topic of the present study relevant.